Evaluasi Daya Simpan Benih Kedelai yang diberi Perlakuan Pelapisan Benih dengan Cendawan Mikoriza Arbuskula - Manggung, Raden Enen Rindi; Ilyas, Satriyas; Bakhtiar, Yenni (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACT The objective of this study was to evaluate the effect of seed coating with arbuscular mychorrhizal fungi (AMF) on viability and vigor of soybean seeds during 6 month storage. This study consisted of two experiments conducted at ambient room and air-conditioned room from May through December 2011. The experiments were arranged in  randomized complete block design with two factors. The first factor was seed coating i.e. untreated control and seed coating using AMF while the second factor was storage period i.e. 0, 1, 2, 3, 4, 5, and 6 months. Results of experiments showed that soybean seeds maintained the viability > 88% after 2 months stored in ambient room and >85% after 4 months stored in air-conditioned room. The viability of untreated and coated seeds did not show significant differences in both experiments. Untreated seeds indicated higher vigor either stored in ambient room (index vigor) or in air-conditoned  room (speed of germination). Seeds coated with AMF showed the rate of increase in moisture content slower than the untreated ones during 6 month storage in ambient room. After 6 month storage in air-conditioned room, the coated seeds had lower moisture content than the untreated. The viability of AMF spores coated on seeds was maintained during 6 month storage in both experiments.Keyword: seed storage, storage room, storage period, viability, vigor